2023
DOI: 10.1088/1361-665x/acae4b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene enhanced flexible piezoelectric transducers for dynamic strain measurement: from material preparation to application

Abstract: In this study, graphene particles are introduced to the lead magnesium niobate-lead titanate (PMN-PT) and polyvinylidene fluoride (PVDF) to form a flexible ternary composite. The graphene concentration is rigorously designed and morphologically optimized, warranting good piezoelectric and dielectric properties. The piezoelectric and dielectric performances are greatly increased compared with the pure PVDF films. Then a theoretical model is formulated to quantitatively interpret the graphene effect on the permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…[104] Graphene-based 2D materials have been used as electrodes or in conjunction with piezoelectric materials to enhance the overall piezoelectric performance of wearable and textile-based PENGs. [105][106][107][108][109] Other 2D materials such as molybdenum diselenide (MoSe 2 ), WS 2 , MoS 2 , and MXene have been studied for their piezoelectric effects in wearable applications. [42,102,110] These investigations have emphasized the promise of 2D materials in wearable energy harvesting applications, notably directing toward the development of textile-based mechanical energy harvesting garments.…”
Section: Mechanical Energy Harvestingmentioning
confidence: 99%
“…[104] Graphene-based 2D materials have been used as electrodes or in conjunction with piezoelectric materials to enhance the overall piezoelectric performance of wearable and textile-based PENGs. [105][106][107][108][109] Other 2D materials such as molybdenum diselenide (MoSe 2 ), WS 2 , MoS 2 , and MXene have been studied for their piezoelectric effects in wearable applications. [42,102,110] These investigations have emphasized the promise of 2D materials in wearable energy harvesting applications, notably directing toward the development of textile-based mechanical energy harvesting garments.…”
Section: Mechanical Energy Harvestingmentioning
confidence: 99%
“…11,12 To achieve high sensitivity or a broad strain range, researchers have explored various elastic materials such as thermoplastic polyurethane, 13−15 hydrogels, 16 PDMS, 2 polyvinyl alcohol, 17 etc. They have employed methods to fabricate flexible strain sensors by combining these materials with conductive fillers, with choices ranging from conductive particles like carbon black, 18 one-dimensional metal nano-wires, 19 and carbon nanotubes 20 (CNTs) to two-dimensional materials such as graphene 21 and MXene, 22 either individually or in combination. 15,23 Zhou et al 24 reported a flexible strain sensor using coaxial wet spinning technology to enhance the strain range by encapsulating carbon nanotubes with thermoplastic polyurethane.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible strain sensors are electronic devices widely used in human-wearable technology and human–machine interaction, playing a crucial role in engineering applications. These sensors have garnered attention for their broad working range, high sensitivity, excellent durability, and stability, finding extensive applications in human motion detection, disease diagnosis, electronic skin, soft robotics, and more. Traditional strain sensors are typically suitable only for smaller working ranges, struggling with large strains and complex deformation environments. , In contrast, flexible strain sensors, unrestricted by the rigidity and brittleness of metals, not only adapt to various strain conditions but also exhibit outstanding mechanical compliance and flexibility, making them suitable for complex, wide-ranging working environments. , To achieve high sensitivity or a broad strain range, researchers have explored various elastic materials such as thermoplastic polyurethane, hydrogels, PDMS, polyvinyl alcohol, etc. They have employed methods to fabricate flexible strain sensors by combining these materials with conductive fillers, with choices ranging from conductive particles like carbon black, one-dimensional metal nanowires, and carbon nanotubes (CNTs) to two-dimensional materials such as graphene and MXene, either individually or in combination. , Zhou et al reported a flexible strain sensor using coaxial wet spinning technology to enhance the strain range by encapsulating carbon nanotubes with thermoplastic polyurethane. Although this sensor achieved a working strain range of 100%, its measured gauge factor (GF) was only 425.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing intelligence of electronic components, the studies on smart materials and their structures have attracted more and more attention of researchers [1,2]. Among them, the applications of graphene in smart composites are the most interesting research [3,4]. Graphene has excellent electrical, mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%